2022
DOI: 10.5507/bp.2022.029
|View full text |Cite
|
Sign up to set email alerts
|

Effect of targeting and generator type on efficacy of extracorporeal shock wave lithotripsy

Abstract: Objective. Analysis of the effect of technical factors, i.e. the type of stone targeting and shock wave generator, on ESWL efficacy. Evaluation of secondary outcomes to determine an optimal strategy for performing the procedure. Patients and Method. In the period from 01/2016 to 07/2021, we analyzed data from patients indicated for ESWL for nephrolithiasis and proximal or distal ureterolithiasis. This was a tricenter retrospective study to evaluate stone-free rates (SFR) while taking into account the number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Fourth, there were differences in stone composition, such as stone density (ranged between 600-1,000 Hounsfield units [HU], except for four studies that did not include stone density data) and stone type (mentioned in two studies). 3,7,8,[12][13][14] Chang et al 4 found that using USG combined with fluoroscopy resulted in a much better SFR, with lower rates of re-treatment and complications. However, it should be noted that several factors have not been assessed in this study, such as stone composition, computed tomography (CT) values, and skin-to-stone distance, which may affect the final result.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourth, there were differences in stone composition, such as stone density (ranged between 600-1,000 Hounsfield units [HU], except for four studies that did not include stone density data) and stone type (mentioned in two studies). 3,7,8,[12][13][14] Chang et al 4 found that using USG combined with fluoroscopy resulted in a much better SFR, with lower rates of re-treatment and complications. However, it should be noted that several factors have not been assessed in this study, such as stone composition, computed tomography (CT) values, and skin-to-stone distance, which may affect the final result.…”
Section: Discussionmentioning
confidence: 99%
“…All studies included stones in the kidney. 12 Only subjects with a mean stone size of <20 mm were included in all studies. The characteristics of the stone type were not mentioned in most studies, except Goren et al 3 who studied children with cystine stones and Arunagiri 13 who examined the type of stone at the end of the ESWL procedure (but not all of the patient's stones can be retrieved).…”
Section: The Characteristics and Quality Of The Studiesmentioning
confidence: 99%